Use of the Instantaneous Wave-free Ratio or Fractional Flow Reserve in PCI - Davies, Justin E; Sen, Sayan; Dehbi, Hakim-Moulay; Al-Lamee, Rasha; Petraco, Ricardo; Nijjer, Sukhjinder S; Bhindi, Ravinay; Lehman, Sam J; Walters, Darren; Sapontis, James; Janssens, Luc; Vrints, Christiaan J; et al. (The New England journal of medicine, 2017)
In this trial involving 2492 patients, coronary revascularization guided by iFR, as compared with fractional flow reserve-guided revascularization, was within the prespecified margin for noninferiority with respect to major adverse cardiac events. For the past 20 years, physiological measurements obtained during invasive procedures have been used to guide coronary revascularization. Pioneering work supported the use of flow measurements to make safe decisions about revascularization, 1 , 2 but this approach was soon superseded by the use of fractional flow reserve (FFR), which measures pressure as a surrogate of flow to estimate the severity of stenosis. 3 – 5 FFR was successful largely because of its technical simplicity and because clinical trials showed that it was associated with improved clinical outcomes after percutaneous coronary intervention (PCI). 6 , 7 Consequently, FFR is now included in the appropriate-use criteria for . . .